2016
DOI: 10.1590/abd1806-4841.20163808
|View full text |Cite
|
Sign up to set email alerts
|

Porphyria cutanea tarda in a HIV- positive patient

Abstract: This is a case report about Porphyria cutanea tarda (PCT) and its relationship with the infection caused by the human immunodeficiency virus (HIV). Cutaneous porphyria is an illness caused by enzymatic modification that results in partial deficiency of uroporphyrinogen decarboxylase (Urod), which may be hereditary or acquired. Several studies suggest that HIV infection associated with cofactors might trigger the development of porphyria cutanea tarda. In this case report, we present a patient infected with HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…In Argentina, PCT patients have a high incidence (16%) of human immunodeficiency virus (HIV) infection ( 11 ). However, since almost all HIV-infected patients have additional risk factors for Porphyria manifestation, it is still unclear whether HIV infection is a precipitating factor for development of PCT.…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, PCT patients have a high incidence (16%) of human immunodeficiency virus (HIV) infection ( 11 ). However, since almost all HIV-infected patients have additional risk factors for Porphyria manifestation, it is still unclear whether HIV infection is a precipitating factor for development of PCT.…”
Section: Introductionmentioning
confidence: 99%
“…PCT typically presents as a chronic, gradually progressive cutaneous disorder, with vesicles, milia, and bullae on the backs of the hands and forearms. 1 Clinical features rarely develop unless there is at least a 75% decrease in the activity of hepatic uroporphyrinogen decarboxylase. PCT is a heterogeneous disease and has been classified into three subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Porphyria cutanea tarda (PCT) a prevalent form of porphyria, typically emerges as an acquired liver disease influenced by exogenous factors, commonly excess alcohol intake, iron overload, chronic hepatitis C, estrogen therapy, and cigarette smoking. 1 The enzymatic activity of uroporphyrinogen decarboxylase (UROD) is crucial for porphyrin metabolism, specifically converting uroporphyrinogen to protoporphyrin. 2 Insufficient functional UROD leads to abnormal accumulation of specific porphyrins in the body, especially in blood vessels, liver, and skin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the different clinical forms of cutaneous scleroderma, sclerodermiform disorders may be secondary to graft versus host disease, drugs, silica exposure, porphyrias, silicone implants, paraneoplastic manifestations, and chronic infections. [1][2][3][4][5][6][7] The authors reported a case of porphyria cutanea tarda (PCT) -or chronic hepatic porphyria, with sclerodermiform lesions, secondary to chronic hepatitis C virus, with significant involvement of photoexposed areas (face and upper limbs). 6 The evolution of PCT with cutaneous sclerodermoid lesions and alopecia is uncommon, and is due to the delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%